The state of the marine environment report for Australia. - Zann, Leon P.; Sutton, David (Canberra, Australia Great Barrier Marine Park Authority, 1995)
Technical annex 2: Pollution
Keywords: Marine pollution; Marine resources conservation; Marine resources